Somatic cell count in milk of Finnsheep ewes and relation with production results - Tyszka, Z. J.; Kramarz, M. (Agricultural and Food Science, 1988)
Finnsheep ewes were tested for milk quality and productivity (lambs and wool) on an experimental farm in two years. Milk samples were taken in first, second and third month of lactation to qualify somatic cell count (SCC) and percentage of fat (F %), protein (P %) and lactose (L %). For the calculation, logarithmic SCC (LSCC) was used. Data concerning rearing of lambs and wool production were calculated with each sample during lactation. Differences in all tested traits were found. Season 1981 proved to be better than 1983. For all observations LSCC was 2.16 and milk composition as follows: F % 5.38, P % 5.42 and L % 4.74. From average ewe there were 2.42 born lambs (6.18 kg), 1.14 weaned lambs (20.09 kg) and 1.24 kg of wool for six months. Correlation coefficients between LSCC and traits tested were; F % 0.07, P % —0.02, L %— 0.53, wool yield — 0.09, number of weaned lambs — 0.01, weight of weaned lambs 0.00. For all above coefficients the error was 0.05. Those tests concerned limited number of animals and will be continued.